Impact of Policies and Programmes of Indian National Congress on the Politics of Jammu and Kashmir: The Impact of Indian National Congress Policies on Jammu and Kashmir Politics (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper we will talk about the Indian National Congress was not set up to surrender its official policy of non-impedance in the inner issues of the local states in light of the fact that the states were autonomous substances under the British law. In this way, the Congress impedance could harm the reasons for the state’s improvement in British India at last that could have influenced the predeterminations of the states. This policy of Congress had suspended the people groups of the states to compose and build up the congress units in the states however they were allowed to turn into the individuals from the Congress and its councils. The Congress anyway changed its policy through state people’s meeting towards states simply after 1935 by erasing the policy of non-impedance from its program and chose to help the states people’s Liberation developments which had been continuing for the fulfillment of their authentic destinations and objectives. The gathering in this manner helped the political powers and gatherings working inside the Princely states working for motivation of socio-political liberation in their separate states. The Congress additionally invited in the states such developments as were probably going to grow all the more rapidly on more extensive premise and drawing quality from the individuals of the states without depending on outside help and help or on the distinction of the Congress.1 Much before they surrendered their policy of nonintervention Nehru was quick to stretch out full help to the opportunity development propelled in Jammu and Kashmir as a result of their non-impedance approach he was not ready to have an immediate contact with the state.